Proceedings of the 1998 American Control Conference. ACC (IEEE Cat. No.98CH36207) 1998
DOI: 10.1109/acc.1998.694625
|View full text |Cite
|
Sign up to set email alerts
|

On the limitations of force tracking control for hydraulic active suspensions

Abstract: This paper presents analysis of a particular force tracking control problem for rectilinear hydraulic actuators governed by a servovalve. It presents no new theory, but rather uses a revealing modell reduction insight coupled with Classical analysis to explain a physical phenomenon. As such, this work is an attempt to explain why a seemingly innocuous problem is more subtle than initially believed. A motivation for this problem is gihen along with prior attempts at a simple solution. The soluiion method evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 10 publications
(2 reference statements)
1
22
0
Order By: Relevance
“…(1) a stick phase occurs when velocity is within a small critical velocity range; (2) there is a maximum value for friction when the mass under consideration sticks.…”
Section: Mechanical Subsystemmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) a stick phase occurs when velocity is within a small critical velocity range; (2) there is a maximum value for friction when the mass under consideration sticks.…”
Section: Mechanical Subsystemmentioning
confidence: 99%
“…Several control algorithms have been used to force tracking for electro-hydraulic actuators [2][3][4], including sliding-mode control [5,6]. These controllers were designed based on the plant physical model and, therefore, the plant parameters knowledge is required.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The force tracking accuracy with the traditional proportional-integral-derivative (PID) type of controller was evaluated by Alleyne et al 10 in 1998 and this simple controller was shown to be inadequate for force tracking because of the fixed control gains used. To cope with the defects of conventional PID controller, some modifications such as fuzzy PID controller, 11,12 fuzzy intelligent feedforward controller, 13 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Alleyne et al [4] showed that a conventional Pill controller does not yield reasonable performance over a wide range of operating conditions. Chen et a!.…”
Section: Introductionmentioning
confidence: 99%